French Philological Detective as a New Subgenre of Criminal Literature (by the Example of F. Vargas Novels) - A. S. Bubnova (Научный диалог, 2020)
The novelty of this study is in the fact that for the first time the characteristic features of the new detective subgenre, the philological detective, are described. The material for the study was the cycle of novels by the French author F. Vargas. The main reasons for the emergence of a philological detective story as a subgenre are revealed. They include a paradoxical combination of canonicity and variability, the ability to adapt to the reader’s expectations, the desire for originality and time features. It is proved that, unlike other detective subgenres, genre-forming components in the philological detective affect and change not the content, but the form, namely, the language material. The French philological detective by F. Vargas is compared with his chronological predecessor, the ironic detective by F. Dar. The idea is expressed that in ironic detectives the linguistic component does not affect the development of the plot and is secondary to it, while in the philological detective story the linguistic component is embedded in the plot and comes to the fore. A brief explanation of the characteristic features of the new subgenre is given: bilingualism, word-creation, author’s neologisms, barbarism, a rich vocabulary of heroes. The opinion is expressed that the above traits are enough to distinguish philological detectives into a separate category.